Comparing the three states of Dhikr, meditation, and thinking about God: an fMRI study - Saraei, Mohammadamin (Religion, brain & behavior, 2023)
Objectives: While there are researches on the neural processes of some religious/spiritual practices like mindfulness meditation, no fMRI research on brain functions of mindfulness in Islam is available. Methods: In this study, by using a 3T MRI machine and recruiting 31 (16F) mentally and physically healthy and highly religious individuals, we performed four different tasks during the fMRI: doing Islamic Dhikr, listening to a voice on body scan meditation, freely thinking about God, and being in resting state. The brain activations relevant to these four conditions were estimated and later compared. Results: Twenty-two distinct neural networks of brain activations were observed. Several brain areas showed similar activations between the four conditions, such as the angular gyrus and parahippocampus. A few areas were only different in resting state, such as caudate and anterior cingulate. The three tasks also showed differences such as in precuneus and posterior cingulate. Discussion: This study demonstrates similarities and differences between the three spiritual tasks and how they lead to transcendent experiences and emotional regulation. It also suggested that Muslims do these three mindfulness practices in a non-directive way, resulting in an increased activity of the default mode network.